Osthole suppresses prostate cancer progression by modulating PRLR and the JAK2/STAT3 signaling axis - Yan, Linjun; Mei, Jiaqi; He, Yuanqiao; Cui, Qi; Wang, Xiaohong; Lv, Feng; Cao, Keyue; Shao, Yuanjian (Frontiers in Oncology, 2025)
BackgroundProstate cancer is a common malignancy in men with limited effective treatment options, highlighting an urgent need for novel therapeutic approaches. Osthole, a natural coumarin compound with antitumor properties, has shown potential in targeting various cancers.MethodsWe conducted the study using a combination of network pharmacology, in vitro assays, and in vivo experiments. First, network pharmacology was used to predict the potential targets of Osthole, identifying 68 targets shared with prostate cancer, including AKT1, TNF, IL6, STAT3, and CTNNB1. Subsequently, we confirmed these targets and assessed the effects of Osthole on cell proliferation, migration, and apoptosis using the Cell Counting Kit-8 (CCK-8) and transwell invasion assays. Meanwhile, molecular docking and western blot analysis were employed to analyze molecular interactions and protein expression levels.ResultsOur findings revealed that Osthole significantly inhibited prostate cancer cell proliferation and migration in a dose-dependent manner and reduced tumor volume in in vivo assays. Western blot analysis indicated that Osthole downregulated PRLR expression and decreased the phosphorylation of JAK2 and STAT3, suggesting the inhibition of the JAK2/STAT3 signaling pathway.ConclusionThese results collectively highlight the therapeutic potential of Osthole in targeting prostate cancer cells through PRLR and modulating the JAK2/STAT3 signaling pathway, warranting further clinical exploration.